PENERAPAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM DALAM IKATAN PELAJAR MUHAMMADIYAH - Mawaddatun Nisa'; Noor Amirudin (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2023)
The values of Islamic religious education, which consist of the values of aqidah, sharia and morals, are an inseparable unity. Aqidah is related to beliefs or beliefs, Sharia is related to regulations that describe the function of religion, while morals are related to one's actions or behavior. Islamic religious education and its values need to be instilled from an early age both in the family and school environment. The values of Islamic religious education are not only obtained through formal education, but can also be obtained from non-formal education which can also be interpreted as education that is often found in the community or organizations that oversee student activities. One example of this non-formal education is the Muhammadiyah Student Association (IPM). This study aims to analyze the application of aqidah values in Muhammadiyah student associations, the application of sharia values in Muhammadiyah student associations, and the application of moral values in Muhammadiyah student associations. This research method is qualitative, with the type of research being a case study. Data sources are primary and secondary, while data collection techniques are through observation, interviews and documentation. Data analysis includes reduction, data display, and conclusion drawing/verification. The results of this study are 1) the application of aqidah values is carried out through the Friday charity work program, 2) the application of sharia values is carried out through the implementation of the nisaiyah/keputrian work program, and 3) the application of moral values is carried out through the LDKS work program